2019
DOI: 10.3390/nu11112583
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Disease Activity, BMI and Phase Angle with Vitamin D Deficiency in Patients with IBD

Abstract: Hypovitaminosis D is frequently present in inflammatory bowel disease (IBD) with a higher incidence in Crohn’s disease (CD) than in Ulcerative Colitis (UC). Given the involvement of the alimentary tract, many factors can contribute to hypovitaminosis D. The aim of the study was to investigate the association of disease activity, body mass index (BMI) and phase angle with vitamin D deficiency in patients with IBD. A cross-sectional study was conducted on a cohort of 206 IBD patients (October 2016–September 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 59 publications
1
20
1
2
Order By: Relevance
“…This could be acknowledged as another limitation. Nevertheless, some other studies did not find a strong association between BMI and disease activity and prognosis[ 20 - 23 ], and this underlines how this topic is still debated and with conflicting evidences.…”
Section: Discussionmentioning
confidence: 95%
“…This could be acknowledged as another limitation. Nevertheless, some other studies did not find a strong association between BMI and disease activity and prognosis[ 20 - 23 ], and this underlines how this topic is still debated and with conflicting evidences.…”
Section: Discussionmentioning
confidence: 95%
“…Supplementation of vitamin D in IBD patients is challenging due to nutrients malabsorption issues, and higher doses are often necessary to achieve the recommended circulating level (above 20 ng/mL, according to IOM) [ 70 ]. Nevertheless, it seemed to be a promising complementary treatment that may improve inflammation markers, such as high-sensitivity C-reactive protein (hs-CRP) and erythrocyte sedimentation rate (ESR), suppressing the Th1 immune response, while reduced clinical disease activity index [ 14 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Vitamin D Critical Role In Ibdmentioning
confidence: 99%
“…An observational study with 206 IBD patients showed that vitamin D deficiency and insufficiency were observed in both CD and UC patients, but were more frequent in CD patients. In addition, moderate and severe clinical disease activities reported were significantly associated with vitamin D deficiency in CD [86]. Similarly, Mechie et al reported that the majority of IBD patients had vitamin D deficiency and the serum levels of 25(OH)D may be considered an important marker for IBD disease activity, in addition to hs-CRP and fecal calprotectin [87].…”
Section: Vitamin D and Gut Microbiota Modulationmentioning
confidence: 97%